Homeology of sex chromosomes in Amazonian Harttia armored catfishes supports the X-fission hypothesis for the X1X2Y sex chromosome system origin - de Menezes Cavalcante Sassi, Francisco; Sember, Alexandr; Deon, Geize Aparecida; Liehr, Thomas; Padutsch, Niklas; Oyakawa, Osvaldo Takeshi; Vicari, Marcelo Ricardo; Bertollo, Luiz Antonio Carlos; Moreira-Filho, Orlando; de Bello Cioffi, Marcelo (Scientific reports, 2023)
The Neotropical monophyletic catfish genus Harttia represents an excellent model to study karyotype and sex chromosome evolution in teleosts. Its species split into three phylogenetic clades distributed along the Brazilian territory and they differ widely in karyotype traits, including the presence of standard or multiple sex chromosome systems in some members. Here, we investigate the chromosomal rearrangements and associated synteny blocks involved in the origin of a multiple X1X2Y sex chromosome system present in three out of six sampled Amazonian-clade species. Using 5S and 18S ribosomal DNA fluorescence in situ hybridization and whole chromosome painting with probes corresponding to X1 and X2 chromosomes of X1X2Y system from H. punctata, we confirm previous assumptions that X1X2Y sex chromosome systems of H. punctata, H. duriventris and H. villasboas represent the same linkage groups which also form the putative XY sex chromosomes of H. rondoni. The shared homeology between X1X2Y sex chromosomes suggests they might have originated once in the common ancestor of these closely related species. A joint arrangement of mapped H. punctata X1 and X2 sex chromosomes in early diverging species of different Harttia clades suggests that the X1X2Y sex chromosome system may have formed through an X chromosome fission rather than previously proposed Y-autosome fusion.
Keywords: Y Chromosome; Catfishes; Phylogeny; In Situ Hybridization, Fluorescence; chromozom Y; Sex Chromosomes; Animals; pohlavní chromozomy; sumci; hybridizace in situ fluorescenční; zvířata; fylogeneze